Single-Cell Analyses of Human Eosinophils at High Resolution to Understand Compartmentalization and Vesicular Trafficking of Interferon-Gamma - Carmo, Lívia A. S.; Bonjour, Kennedy; Spencer, Lisa A.; Weller, Peter F.; Melo, Rossana C. N. (Frontiers in Immunology, 2018)
Human eosinophils release numerous cytokines that are pre-synthesized and stored within their cytoplasmic specific (secretory) granules. For example, high levels of interferon-gamma (IFN-γ) are constitutively expressed in these cells, but the intracellular compartments involved in the transport and release of this cytokine remain to be established. In this work, we used a single-cell approach to investigate the subcellular localization of IFN-γ in human eosinophils stimulated or not with tumor necrosis factor alpha (TNF-α) or CC-chemokine ligand 11 CCL11 (eotaxin-1), inflammatory mediators that induce eosinophil activation and secretion. A pre-embedding immunonanogold transmission electron microscopy (TEM) technique that combines optimal epitope preservation and access to membrane microdomains was applied to detect precise localization of IFN-γ in combination with computational quantitative analyses. In parallel, degranulation processes and formation of Eosinophil Sombrero Vesicles (EoSVs), large transport carriers involved in the transport of granule-derived cytokines, were investigated. Quantitative TEM revealed that both CCL11 and TNF-α-activated eosinophils significantly increased the total number of EoSVs compared to the unstimulated group, indicating that this vesicular system is actively formed in response to cell activation. Ultrastructural immunolabeling identified a robust pool of IFN-γ on secretory granules in both unstimulated and stimulated cells. Moreover, EoSVs carrying IFN-γ were seen around or/and in contact with secretory granules and also distributed in the cytoplasm. Labeling was clearly associated with EoSV membranes. The total number of IFN-γ-positive EoSVs was significantly higher in stimulated compared to unstimulated cells and these labeled vesicles had a differential distribution in the cytoplasm of activated cells, being significantly higher in the cell periphery compared with the inner cell, thus revealing intracellular IFN-γ mobilization for release. IFN-γ extracellular labeling was found at the cell surface, including on extracellular vesicles. Our results provide direct evidence that human eosinophils compartmentalize IFN-γ within secretory granules and identify, for the first time, a vesicular trafficking of IFN-γ associated with large transport carriers. This is important to understand how IFN-γ is trafficked and secreted during inflammatory responses.